Shades of lightweight: Supporting cross-generational communication through home messaging - Lindley, Siân (Universal Access in the Information Society, 2012)
Previous work suggests that older adults view communication with family as being worthy of time and dedication, and that they fail to understand the allure of lightweight contact. This paper presents findings from a field trial in which three generations of a family were linked through situated messaging devices, which, while designed to support lightweight messaging, also afford rich and expressive contact. Analysis suggests that communication via the devices provided a valuable additional dimension to the families’ existing practices, but that the type of messaging supported is best understood as one element in an amalgam of communication possibilities. Suggestions for complementary approaches are offered.